Discrepancies between students' and teachers' expectations of purposeful foreign language learning - Wijaya, Henry (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
Motivation has been found to play a pivotal role for the success of foreign language learning. Students generally stay motivated if they appreciate the purposefulness of their learning process, so if they did not share the same expectations with their teachers of the process, these discrepancies might affect their motivation and disrupt their learning. This mixed-method research uses online questionnaires to examine four major topics, namely program, curriculum, teachers, and students, and employs comparative analysis to the views of the two respondent groups to investigate such discrepancies. The results show discrepancies exist among the respondents, especially in what the students expect to learn, the line of work that they desire to take, and the different factors that affect their motivation. These results signify the need to better align the students' and the teachers' expectations of foreign language learning in order to maintain the students' motivation and to improve the effectiveness of the learning process.